Regional Development of Maritime Tourism and Accessibility Gap of North Buton, South East Sulawesi, Indonesia - Isfa Sastrawati, Ihsan; V. Patandianan, Marly; V. Natalia, Venny; Pati, Sakka (International Journal of Engineering and Technology, 2024)
Indonesiaâ€™s decentralised authority policy inspire the application of local economic development approach in many region which drive the economic growth base on their natural resources. As a maritime region, North Buton has a potential coastal area that can be explored as a tourism industry. This sector is one of the economic catalysts that succeed in many regions and countries in the world. North Buton has many potential in maritime tourism resources but many of them remain concealed or undeveloped due to the lack of transport services. Accessibility is the main feature in tourism industry, this reason drive the purposes of this research, that is, identify the maritime tourism destinations and the accessibility services and development in the North Buton Region. The research used spatial analysis by using Geographical Information Systems (GIS) and photo mapping. The tourism destinations were identified by considering the availability of attractions, amenities, and access. Then, accessibility was identified by measuring the distances, time and routes of transportation to reach the tourism destinations.Â The results of the analysis showed that there are 28 kind of maritime tourism objects which lay along the North Buton urbanized coastal area. Most ofÂ the objects can be achievedÂ with longer land trip round the region. The shorter route uses sea transport is high potential but not available yet. Â Â